HEALTH CAPITAL AND POPULATION AGEING: FINANCIAL AND ECONOMIC CONSEQUENCES FOR THE LABOUR MARKET - Volodymyr Tytykalo; Viktoriia Marhasova; Nina Petrukha; Nataliia Tkalenko; Serhii Petrukha; Anastasiia Orlovska (Financial and credit activity problems of theory and practice, 2026)
The process of population ageing is one of the significant demographic risks that affects the state of the labour market and long-term economic sustainability. Accordingly, it is relevant to study the concept of Health Capital in the context of the impact of population ageing on financial and economic processes in the country. The purpose of the article is to substantiate the essence of the concept of Health Capital in the context of population ageing and assess its economic impact on the development of the labour market. The hypothesis of the study is that the development of the concept of Health Capital at the national level affects the reduction of macroeconomic risks, in particular, population ageing, by improving the quality of human capital, strengthening the labour supply, and enhancing labour market resilience. To test this hypothesis, economic and statistical analyses and multiple linear regression modeling were conducted. Based on the results obtained, a relationship between the concept of Health Capital and labour market indicators was confirmed. The developed econometric model explains 73.9% of changes in the employment rate. In particular, life expectancy and per capita healthcare spending have a statistically significant positive impact on employment. Healthcare spending as a share of GDP has a negative relationship with the employment rate. This relationship is explained by the fact that an increase in the share of healthcare spending does not always have a positive effect on the labour market. According to the current state of development of the healthcare system, such an increase is associated with macroeconomic imbalances and the military-political situation. Among the analyzed indicators, per capita healthcare spending has the most significant impact on employment outcomes. The findings confirm that Health Capital represents a strategic component of human capital and a significant determinant of labour market resilience and sustainable socio-economic development. Under conditions of martial law and post-war recovery, strengthening investment in healthcare, rehabilitation services, and preventive healthcare, alongside the improvement of financial mechanisms for supporting population health, can contribute to preserving labour potential, sustaining economic activity, mitigating the consequences of demographic ageing, and enhancing the long-term economic resilience of Ukraine.